C-REACTIVE PROTEIN AND ADIPOSITY IN WOMEN WITH POLYCYSTIC OVARY SYNDROME - Fathi, Fatimah Haitham (Journal of medical and pharmaceutical sciences, 2018)
C-reactive protein (CRP) is one of the biomarkers that elevated in obese women with polycystic ovary syndrome (PCOS). PCOS is the most common endocrine disorder, affecting 5-10% of women at reproductive age. This syndrome is characterized by overproduction of androgen and ovulatory dysfunction which are accompanied by many clinical and biochemical features including hirsutism, acne, ovary cysts, menstrual irregularities, obesity, dyslipidemia, hyperinsulinemia and glucose intolerance. This study was aimed to: 1. measure serum levels of CRP, total cholesterol, triglyceride, LDL, HDL, VHDL, in addition to calculate Body Mass Index (BMI), in women with PCOS and to compare the results with that of healthy women (Controls). 2. Compare serum CRP, total cholesterol, triglyceride, LDL, HDL and VHDL in patient subgroups with BMI matched control subgroups. The present study includes thirty (30) women with PCOS and thirty (30) healthy women served as control. All subjects' age range was between 15 to 40 years, then each group classified into two subgroups depending on BMI. Blood samples were collected and serum was obtained to measure CRP and lipid profile. Polycystic ovarian women group exhibited significantly increased serum levels of   CRP (p= 0.001), cholesterol (p= 0.009), triglyceride (p=0.0001) and LDL (p= 0.0001) when compared to healthy control group. BMI also increased in polycystic ovarian women group although it is statistically not significant when compared to controls. Our results indicated that CRP is one of biomarkers in obese women with PCOS. Its high level associated with adiposity rather than PCOS itself.
Keywords: Polycystic ovary syndrome; Adiposity; C-reactive protein; lipid profile; BMI